PENGEMBANGAN INFRASTRUKTUR JARINGAN BERBASIS NIRKABEL KE JARINGAN BERTEKNOLOGI GPEN (GIGABIT PASSIVE ETHERNET NETWORK) DI KAMPUS IAIN BENGKULU - Wijaya, Candra; Aspriyono, Hari; Al Akbar, Abdussalam (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2021)
The purpose of this research is to build an interconnection network using GPEN (Gigabit Passive Ethernet Network) technology so as to provide convenience for network admin users in managing, controlling, and maintaining each client, making it easy for network technicians when a breakdown occurs, and Providing easy client user authentication in the area (PUSKOM) IAIN Bengkulu. The research method used is research and development research, the research method used to aim at developing, producing products and waiting for the effectiveness of the research method. Developing a wireless-based network, namely a point-to-point radio to a network with GPEN technology (Gigabit Passive Ethernet Network) as a switch and router that supports gigabit ports and to control and monitor bandwidth on each client. Better network quality and efficiency so that activities such as browsing, uploading and downloading are faster.